Spiritual Journeys in Symbolic Language (A Study of the Differences and Similarities of Spiritual Journeys in Sohrewardi’s Treatises and Attar’s Mosibatnameh) - Khalilnia, Zahra (2019)
In most of mystical works, the wayfarer of the Path of Truth is in one stage of the journey. Human spirit or rational soul, after becoming conscious of its own loneliness in the world of darkness and the prison of body as well as its occidental exile visits to heavenly principle, which is the guiding angel, becomes aware of the obstacles in its way back to the Orient and its own existential origin. Four Journeys is one of those issues which has been taken into account in the works of great sages like Avicenna and renowned mystics. The current study was an effort for conducting a comparative study of the stages of Four Journeys in Sohrewardi’s treatises and Attar’s Mosibatnameh in view of their differences and similarities via a descriptive method. Through this study, it was intended to cast light on the importance of man’s knowledge of universe and himself focusing on acquired knowledge and external senses and inner perceptual faculties. The main hero of Sohrewardi in all of his treatises in guidance of man is intellect which emerges in the guise of a Spiritual Guide in order to guide the wayfarer. While in Attar’s Mosibtanameh, despite intellect, the role of prophets and particularly the Holy Prophet of Islam is highlighted in the guidance of man and his reaching to the destination of the journey. In fact, intellect in the views of both thinkers is Active Intellect or Tenth Intellect whose place is in human heart and Sohrewardi has used the beautiful term “Red Intellect” to refer to it.